2009
DOI: 10.1080/02699200902839818
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of phonetic inventory complexity in acquisition of Spanish: Implications for phonological universals

Abstract: This study evaluates 39 different phonetic inventories of 16 Spanish-speaking children (ages 0;11 to 5;1) in terms of hierarchical complexity. Phonetic featural differences are considered in order to evaluate the proposed implicational hierarchy of Dinnsen et al.’s phonetic inventory typology for English. The children’s phonetic inventories are examined independently and in relation to one another. Five hierarchical complexity levels are proposed, similar to those of English and other languages, although with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…In the analysis of whole-word templates, differences were observed in the production of codas and in place variegation: monolingual German children displayed more templates with codas and monolingual Spanish children displayed more melody templates. These results are consistent with numerous studies which report salient cross-linguistic differences between Spanish versus English/German children in their production patterns (Cataño et al, 2009;Lleó, 2008;Lleó & Demuth, 1999;Lleó et al, 1996Lleó et al, , 2003. Specifically, Lleó et al (1996), using a similar database to the current one, found that German-speaking children produced significantly more codas than Spanish-speaking children at the 25-word point; and Cataño et al (2009) found that /l/ was present in the early phonetic inventories of Spanish-speaking children but not in those of English-speaking children, a finding that is relevant to this study, since German may pattern similarly to English in the development of laterals.…”
Section: Output Patterns and Templatessupporting
confidence: 95%
“…In the analysis of whole-word templates, differences were observed in the production of codas and in place variegation: monolingual German children displayed more templates with codas and monolingual Spanish children displayed more melody templates. These results are consistent with numerous studies which report salient cross-linguistic differences between Spanish versus English/German children in their production patterns (Cataño et al, 2009;Lleó, 2008;Lleó & Demuth, 1999;Lleó et al, 1996Lleó et al, , 2003. Specifically, Lleó et al (1996), using a similar database to the current one, found that German-speaking children produced significantly more codas than Spanish-speaking children at the 25-word point; and Cataño et al (2009) found that /l/ was present in the early phonetic inventories of Spanish-speaking children but not in those of English-speaking children, a finding that is relevant to this study, since German may pattern similarly to English in the development of laterals.…”
Section: Output Patterns and Templatessupporting
confidence: 95%
“…A case in point is offered by Pye et al (1987): in Quiché /l/, /tʃ/ and /χ/ have a much higher IF/FL than in English, and these consonants are acquired sooner by Quiché-speaking than by Englishspeaking children, hence confirming the impact of FL of consonants in the ambient language on consonant development. A similar finding is reported by Catano et al (2009): Spanishspeaking children acquire the liquid /l/ earlier than English-speaking children, because /l/ has a higher FL and token frequency in Spanish than in English.…”
Section: Teasing Apart Multiple Determinants Of Acquisition Ordersupporting
confidence: 86%
“…distinguishing words and their meanings, plays a role in their acquisition. The impact of the FL was already established for the development of consonants in children acquiring English, Quiché, Arabic and Spanish (Amayreh & Dyson, 2000;Catano et al, 2009;Stokes & Surendran, 2005). However, no such effect was found for children acquiring Cantonese (Stokes & Surendran, 2005).…”
Section: Effect Of Ambient Language On Age Of Acquisition Of Word-inimentioning
confidence: 96%
“…Early phonetic inventories included labial and coronal place; stop, nasal, and glide consonant manner types; mid and low front vowels; and CV and CVCV open syllable shapes. These characteristics were also observed in children learning languages other than English (e.g., Arabic, Mandarin, Spanish, and Korean) in several cross-linguistic studies (Amayreh & Dyson, 2000;Cataño, Barlow, & Moyna, 2009;Cen & Kent, 2005;Lee, Davis, & MacNeilage, 2010). They have also been noted in hearing-impaired children (Warner-Czyz, Davis, & Morrison, 2005).…”
Section: Phonetic Approachesmentioning
confidence: 75%